2015
DOI: 10.1111/medu.12621
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of validity evidence for checklists versus global rating scales in simulation-based assessment

Abstract: Checklist inter-rater reliability and trainee discrimination were more favourable than suggested in earlier work, but each task requires a separate checklist. Compared with the checklist, the GRS has higher average inter-item and inter-station reliability, can be used across multiple tasks, and may better capture nuanced elements of expertise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
193
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(212 citation statements)
references
References 81 publications
6
193
1
12
Order By: Relevance
“…The thoroughly tested objective structured assessment of technical skill format allows for graduated judgments of competence, as well as registration of an overall impression of incompetence caused by one or more errors that only result in a minimal reduction in the checklist score. Furthermore, the dichotomous nature of checklists introduces a significant ceiling effect that is unsuitable for measuring nuances of proficiency [21,22]. WAHIDI et al [23] used a checklist to assess when 13 trainees could independently perform a successful EBUS-TBNA procedure, and found that 25%, 50%, and 75% of the trainees did so after an average of five, nine, and 13 procedures, respectively.…”
Section: Validity Evidence For the Assessment Toolmentioning
confidence: 99%
“…The thoroughly tested objective structured assessment of technical skill format allows for graduated judgments of competence, as well as registration of an overall impression of incompetence caused by one or more errors that only result in a minimal reduction in the checklist score. Furthermore, the dichotomous nature of checklists introduces a significant ceiling effect that is unsuitable for measuring nuances of proficiency [21,22]. WAHIDI et al [23] used a checklist to assess when 13 trainees could independently perform a successful EBUS-TBNA procedure, and found that 25%, 50%, and 75% of the trainees did so after an average of five, nine, and 13 procedures, respectively.…”
Section: Validity Evidence For the Assessment Toolmentioning
confidence: 99%
“…Por exemplo, para a mensuração do segundo nível de Kirkpatrick (aprendizagem), pode-se fazer uso de diferentes de formatos de avaliação na simulação: desde pré-teste e pós-teste com avaliação simples do conhecimento teórico, a avaliações por vídeo com uso de checklist ou por avaliação global [13,43]. Há ainda a proposta [14,52].…”
Section: /11unclassified
“…Para uma avaliação mais precisa quanto à eficiência dos diferentes formatos de simulação, sob uma perspectiva instrucional, é necessária ainda uma melhor definição quanto aos critérios de mensuração do impacto de cada um dos elementos instrucionais para desenvolvimento cognitivo do aprendiz [43,49]. O treinamento em simulação na saúde tem o potencial de sobrecarregar a memória de trabalho, uma vez que pode apresentar objetivos de aprendizagem cognitivos, psicomotores, atitudinais de forma isolada ou em combinação.…”
Section: Estudos Comparativos Sobre Formatos Instrucionais Em Simulaçãounclassified
“…With expert raters, GRS may in fact be more reliable than checklists. [21][22][23] However, there was variability in the reliability of individual steps. We could not assess relationship to other variables, as the task included no alternative performance measures, nor can we offer evidence of consequences validity.…”
Section: Evidence For Validitymentioning
confidence: 99%